2010
DOI: 10.1029/2010wr009442
|View full text |Cite
|
Sign up to set email alerts
|

Shopping for hydrologically representative connectivity metrics in a humid temperate forested catchment

Abstract: [1] In order for connectivity to serve as an effective diagnostic classification tool of hydrological behavior, it clearly matters (1) how it is measured and (2) whether the chosen measures are correlated not only to catchment-scale antecedent moisture conditions but also to streamflow discharges. Previous studies have advocated that connectivity in shallow soil moisture patterns induces threshold-like changes in runoff in temperate rangeland catchments but not in temperate humid forested catchments. We argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
111
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 60 publications
1
111
1
Order By: Relevance
“…1). It is worth noticing that a similar evolution occurred simultaneously in the neighboring fields of surface hydrology [13][14][15][16][17][18][19][20], geomorphology [21][22][23][24], landscape ecology [25][26][27][28], pore scale or soil physics [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). It is worth noticing that a similar evolution occurred simultaneously in the neighboring fields of surface hydrology [13][14][15][16][17][18][19][20], geomorphology [21][22][23][24], landscape ecology [25][26][27][28], pore scale or soil physics [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The word connectivity is often used as a broad concept with various definitions related for example to the efficiency with which runoff moves from source areas to streams [35] or to the presence of an unsaturated zone between a river and an underlying aquifer [36]. Therefore, as pointed out by several authors [37,18,19], there is a need to adopt some standards and to share them.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade there have been numerous attempts to characterise the connectivity/disonnectivity dynamic (Ali and Roy, 2010;Meerkerk et al, 2009;Michaelides and Chappell, 2009;Tetzlaff et al, 2007). Pringle (2003b) noted the variety of definitions of connectivity, used across and within disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…number of days elapsed since the last rainfall intensity exceeding 30 mm/d) appeared to be the most influential surrogate measure for AMCs: the smaller the value of DSP 30 , the more likely the presence of 0.85-1.4 ha wide saturation patches at a depth of 15 cm. In a paper aiming to identify hydrologically representative connectivity metrics in the Hermine catchment, Ali and Roy (2010d) found that the spatial connectedness of locations whose volumetric soil moisture content exceeded 30% was rather dependent upon AP 7 (i.e. 7-day antecedent precipitation).…”
Section: Introductionmentioning
confidence: 99%
“…"××" means that a strong significant correlation was found, "×" means that rather weak correlations were found, and blanks mean that no significant correlations were found. Spatial connectivity of locations whose volumetric soil ×× moisture content exceeds 30% Source : Ali et al, 2010d Development of spatially coherent saturation patches on:…”
Section: Introductionmentioning
confidence: 99%